The Role of Parental Attachment and High Screen Use - Edith Gunnarsdóttir 1974- (2014)
Electronic screen use has increased among adolescents in recent years and high electronic screen use has been linked to negative psychological symptoms. The aim of the current study was to investigate the relationship between electronic screen viewing activities among 10 - 13 year old children and parental attachment. The current study analyzed cross sectional, population data from 2013 Youth in Iceland, with 11,267 participants (response rate of 90%). The questionnaire was administered in all middle schools in Iceland. Multiple linear regression model were used to analyze the data. The current results indicate that high electronic screen uses is linked to parental attachment, and high screen use is increasing, especially for boys. The findings in this study provide numerous risk factors that are associated with high electronic screen use. This study is the first of its kind to demonstrate relationship between electronic screen use and parental attachment. Key words: screen use, adolescents, support, monitoring, time with parents Skjánotkun hefur aukist hjá unglingum á undanförnum árum og hefur mikil skjánotkun verið tengd við neikvæð sálræn einkenni. Tilgangur rannsóknarinnar var að rannsaka samband milli skjánotkunar hjá 10 – 13 ára börnum og foreldratengsla. Í rannsókninni voru notuð fyrirliggjandi gögn, Ungt fólk 2013 með 11,267 þátttakendum (svarhlutfall 90%). Könnunin var lögð fyrir í öllum grunnskólum á Íslandi. Línuleg aðhvarfsgreining var notuð til að túlka niðurstöðurnar. Niðurstöður sýndu fram á að tengsl séu á milli mikillar skjánotkunar og foreldratengsla og að skjánotkun er að aukast og sérstaklega hjá strákum. Þessi rannsókn er sú fyrsta sem sýnir fram á samband milli mikillar skjánotkunar og foreldratengsla. Lykilhugtök: skjánotkun, unglingar, stuðningur, eftirlit, tími með foreldrum